Upaya Mempertahankan Kapasitas Membran Reverse Osmosis (RO) pada Instalasi Daur Ulang Air Limbah di Industri Kaleng: Attempts to Maintain Reverse Osmosis (RO) Membrane Capacity in Wastewater Recycling Installations in the Can Industry - RUDI NUGROHO; SATMOKO YUDO; DINDA RITA KRISHUMARTINI HARTAJA; SETIYONO; IKBAL; CITRA ARDIANA (BRIN Publishing (Penerbit BRIN), 2023)
The increasing industrial demand for clean water is in line with the current population growth rate. One industry that has a high demand for clean water is the can industry. This water is widely used especially for the production process. The existing problem is the limited availability of water sources and the uncertainty of supply continuity as well as the increasing operational costs. One alternative solution to the problem of water demand is to optimize the recycled water from the wastewater treatment plant and maintain the capacity of the processed water from the Reverse Osmosis (RO) unit for process needs in the industry. The wastewater recycling treatment process is divided into two stages, namely the production wastewater treatment plant process with chemical and filtration processes, and the recycled water treatment process with the RO process. The RO process water is used for the can washing process. In maintaining the capacity and quality of RO production water, several efforts have been made including; replacing lamella units, cleaning RO membranes, increasing pH values, reducing conductivity values, replacing membranes and others. So, with the maintenance and optimization of RO unit production capacity, the can washing production process will be maintained and also increased. Currently, the installed RO water production capacity is 200 m3/day. One way that has a dominant influence in maintaining this capacity is to replace the lamella unit, which serves to improve the quality of RO raw water, so as to extend the service life of the RO membrane. ABSTRAK Meningkatnya kebutuhan industri akan air bersih sejalan dengan tingkat pertumbuhan penduduk saat ini. Salah satu industri yang mempunyai kebutuhan air bersih tinggi adalah industri kaleng. Air ini banyak dipakai khususnya untuk proses produksi. Permasalahan yang ada adalah ketersediaan sumber air yang terbatas dan ketidakpastian kesinambungan pasokan serta biaya operasional yang terus meningkat. Salah satu alternatif solusi permasalahan kebutuhan air tersebut, adalah dengan mengoptimalkan air hasil daur ulang instalasi pengolahan air limbah dan mempertahankan kapasitas air hasil olahan unit Reverse Osmosis (RO) untuk kebutuhan proses di industrinya. Proses pengolahan daur ulang air limbah terbagi dalam dua tahap, yaitu proses instalasi pengolahan air limbah produksi dengan proses kimia dan filtrasi, serta proses pengolahan air daur ulang dengan proses RO. Air hasil proses RO ini digunakan untuk proses pencucian kaleng. Dalam mempertahankan kapasitas dan kualitas air produksi RO, beberapa upaya telah dilakukan antara lain: mengganti unit lamela, cleaning membran RO, meningkatkan nilai pH, menurunkan nilai konduktivitas, penggantian membran, dan lainnya. Sehingga dengan mempertahankan dan mengoptimalkan kapasitas produksi unit RO, proses produksi pencucian kaleng akan terus terjaga dan juga meningkat. Saat ini kapasitas produksi air RO terpasang sebesar 200 m3/hari. Salah satu cara yang memiliki pengaruh dominan dalam mempertahankan kapasitas tersebut adalah dengan mengganti unit lamela, yang berfungsi untuk meningkatkan kualitas air baku RO, sehingga dapat memperpanjang masa pakai membran RO.